Sister : An African American Life in Search of Justice - White, Sylvia Bell, 1930- (Book collections on Project MUSE., 2012)
Raised with twelve brothers in a part of the segregated South that provided no school for African American children through the 1940s, Sylvia Bell White went North as a teenager, dreaming of a nursing career and a freedom defined in part by wartime rhetoric about American ideals. In Milwaukee, she and her brothers persevered through racial rebuffs and discrimination to find work. Barred by both her gender and color from employment in the city's factories, Sylvia scrubbed floors, worked as a nurse's aide, and took adult education courses. When a Milwaukee police officer killed her younger brother Daniel Bell in 1958, the Bell family suspected a racial murder but could do nothing to prove it - until twenty years later, when one of the two officers involved in the incident unexpectedly came forward. Daniel's siblings filed a civil rights lawsuit against the city and ultimately won that four-year legal battle. Sylvia was the driving force behind their quest for justice. Telling her life story in these pages, Sylvia emerges as a buoyant spirit, a sparkling narrator, and, above all, a powerful witness to racial injustice.